Prohibition of LGBT at the Qatar World Cup According to the Perspective of Qatari Islamic Law - Pratama, Fandi Rakan Surya; Jannah, Shofiatul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The prohibition of LGBT (Lesbian, Gay, Bisexual and Transgender) in the context of the Qatar World Cup is an interesting issue to analyze from the perspective of Qatari Islamic Law. This research aims to analyze the legal basis and arguments underlying the LGBT ban in the context of the 2022 FIFA World Cup in Qatar, with a focus on the Islamic Law perspective which is the basis of the country's law. The research method used is a qualitative approach with analysis of legal documents, including Qatar's constitution and relevant legal regulations. In addition, an interpretive approach to the principles of Islamic law is also applied to understand legal views regarding LGBT in the Qatari context. The research results show that the LGBT ban in the context of the Qatar World Cup is based on an interpretation of Islamic law which considers LGBT practices as a violation of religious values and norms. Qatar's Islamic law emphasizes that same-sex relations are against Islamic teachings and are considered unlawful. The Qatari Islamic Law perspective also emphasizes the importance of maintaining morality and the family which are the foundations of Qatari society. Therefore, the LGBT ban at the Qatar World Cup is seen as an effort to protect religious values and maintain the social integrity of society.